2013
DOI: 10.1177/0956462413487327
|View full text |Cite
|
Sign up to set email alerts
|

Multiple self-report measures of antiretroviral adherence correlated in Sierra Leone, but did they agree?

Abstract: In resource-poor settings, studies validating multiple self-report measures of adherence are limited and do not include data from West Africa. We prospectively assessed the associations between multiple self-report measures of adherence in 58 patients receiving antiretroviral therapy. Self-report measures included a 30-day visual analog scale, 30-day qualitative single-item measure, Adult AIDS Clinical Trial Group 4-day recall, and 3-level categorical 7-day qualitative measure. Unannounced pill count was the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…25 We found that many were illiterate which is also reported in other African settings. 26 When comparing the adherent with the nonadherent participants, none of the demographic variables differed significantly between groups. This may indicate that being illiterate is not a predictor of nonadherence, and this has also been found in other studies.…”
Section: Discussionmentioning
confidence: 91%
“…25 We found that many were illiterate which is also reported in other African settings. 26 When comparing the adherent with the nonadherent participants, none of the demographic variables differed significantly between groups. This may indicate that being illiterate is not a predictor of nonadherence, and this has also been found in other studies.…”
Section: Discussionmentioning
confidence: 91%
“…While we measured adherence to ART for our programme participants throughout the study period, we only measured adherence to ART for a sub-set of individuals receiving standard of care during a three-month period. Additional details of this study are published elsewhere and focus on the adherence to ART for those individuals who were only receiving standard of care (Kelly et al., 2013 ). In this study, we focused on adherence measurement with unannounced pill counts for our study groups (standard of care and community-based ART) over a three-month period ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%